Examining The Modelling Skills of Grade 8 Students on The System of Linear Equation in Two Variables through Problem-Based Learning Model - Amal, Ikhlasul; Fadhiliani, Dwi; Hasbi, M. (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2024)
Mathematical modeling is the process of solving a problem in the real world by simplifying it into mathematical form. Mathematical modeling skills are very useful for students in developing knowledge and deepening their concepts. In learning, this ability is needed in solving contextual problems. However, many students have difficulty in simplifying problems into mathematical models, especially in the material of the Two-Variable Linear Equation System (SPLDV). Applying the Problem Based Learning model is one of the efforts to improve students' mathematical modeling skills. This research uses a quantitative approach and uses a Pre-Experimental Design type of One-Group Pretest-Posttest Design. This study involved all VIII grade students in one of the schools in Aceh Besar. 31 students were selected as samples, and random sampling technique was used. . The instrument in this study was a test question on mathematical modeling ability. Furthermore, one-party t-test was used to analyze the data obtained. The results showed that the Problem Based Learning model improved students' mathematical modeling skills on SPLDV material. It is important for teachers to continue to hone students' modeling skills by getting students used to solving everyday problems using mathematical models so as to improve students' mathematical modeling skills. Improving students' modeling skills is one of the strategies to develop students' mathematical problem solving skills which are the foundation of meaningful learning.